2022
DOI: 10.7860/jcdr/2022/51552.16192
|View full text |Cite
|
Sign up to set email alerts
|

Joint Manifestations Following COVID-19 Infection- A Case Series of Six Patients

Abstract: A rare subset of Coronavirus Disease-2019 (COVID-19) positive patients has musculoskeletal manifestations including arthritis, arthralgia, myalgia and non specific body aches. Moreover, postviral Reactive Arthritis (ReA) has been reported following COVID-19 infection. This article reports the characteristic joint manifestations of Severe Acute Respiratory Syndrome-Corona Virus-2 (SARSCoV-2) infection in 6 out of 211 consecutive patients with laboratory-confirmed diagnosis of COVID-19 and treated at dedicated h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…The interval between COVID‐19 symptoms and the onset of arthritis differs from zero days (simultaneous with COVID‐19) to 3 months. The onset of arthritis in 2 cases occurred less than 1 week (≤1 week) after COVID infection, 54 and 16 happened after 1 week 16–23,30,41,43,51,53,55 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The interval between COVID‐19 symptoms and the onset of arthritis differs from zero days (simultaneous with COVID‐19) to 3 months. The onset of arthritis in 2 cases occurred less than 1 week (≤1 week) after COVID infection, 54 and 16 happened after 1 week 16–23,30,41,43,51,53,55 …”
Section: Resultsmentioning
confidence: 99%
“…Prescribed forms of steroids were not noted in 2 cases 54 . HCQ as a kind of DMARDs was administered in 1 case 51 . All prescribed drugs are listed in Table 3, and 1 patient's arthritis subsided without treatment 17 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The exact terminology varied between studies and, for the purposes of this review, reported iRMDs have been grouped according to the ICD-11 categories: RA, polymyalgia rheumatica and giant cell arteritis, adult-onset Still disease, juvenile idiopathic arthritis, inflammatory spondylarthritis, SLE, systemic sclerosis, idiopathic inflammatory myopathy, vasculitis, psoriatic arthritis, direct infection of joint, and inflammatory arthropathies unspecified. In the case reports and case series, the most commonly reported iRMDs were "reactive arthropathies" (n = 47), 14, followed by "inflammatory arthropathies unspecified" (n = 18), 15,23,24,38,[44][45][46][47][48][49][50][51][52] RA (n = 12), [53][54][55][56][57][58][59][60][61][62] and SLE (n = 11). 6,59,[63][64][65][66][67][68][69][70][71] The single observational (cross-sectional) study by Taha et 37 out of 100 people observed (37%) developed "post COVID arthritis."…”
Section: Resultsmentioning
confidence: 99%
“…There were 26 studies that proposed mechanisms related to the initiation of an autoimmune process. 6,10,15,[22][23][24]31,33,38,39,45,48,49,55,56,58,65,67,[69][70][71][73][74][75][76][77] Several studies proposed multiple possible autoimmune mechanisms. 10,24,31,39,45,48,55,73,77 Proposed mechanisms included molecular mimicry, 10,15,23,24,31,33,39,45,48,58,65,69,[73][74][75][76]…”
Section: Resultsmentioning
confidence: 99%